Lapu-lapu Chemicals Company - Cham, Teng Peng; Go, Homer U.; Sy, Francisco L. (Diliman, Quezon City College of Engineering, 1964)
Plant site: Mactan Island -- Plant area: 10 hectares -- Capital investment: 1,474,166 pesos -- Total annual sales at maximum production: 1,758,592 pesos -- Manufacturer cost at maximum capacity: 1,125,050 pesos -- Profit before taxes: 633,542 pesos -- Pay-off time: 2.33 years -- Break-even point: 27.2% or .653 tons/day -- Shut-down point: 12.8% or .307 tons/day
Plant design.
Typescript
Submitted in partial fulfillment of the requirements in ChE 62 Chemical Engineering Plant Design.
Keywords: Factories -- Design and construction; Chemical plants; Hydrofluoric acid; Fluorides